Cognitive Effects of the Computational Paradigm in the Human Sciences. - Gardin, Jean-Claude (Facets of Rationality, 1995)
The article discusses the cognitive effects of the computational paradigm in the human sciences. Computer applications are known in all sectors of the human sciences. The most common functions served by computers are sorting and counting i.e., clerical or mathematical operations in which the traditional contest of "mind versus machine" tends to turn in favor of the latter. However, the output of mechanical sorting and counting is seldom a finished product: it has to be interpreted and evaluated in a variety of ways, in which the mind regains the upper hand. The situation is different to a particular class of simulations in which the object under study is the mental behavior of the scientist rather than the sociocultural phenomena that he or she has chosen to explore. No one will be surprised at the importance given to the matter of representation. Collecting the various bits and pieces of the database scattered in a given paper is not an easy task. Displaying them as the semiotic base of the formal construct leads to further difficulties, as the exercise brings into focus the extreme variability of scholarly practice in this respect. Given a set of material or textual objects, there seems to be no such thing as a common language in the way they are represented in different papers. Needless to say, arguments are not lacking in defense of variability, the more worthy from a scientific viewpoint being the well-established relation between representation systems and the theories which are made to rest upon them.